Reactive Molecular Dynamics Simulations of Iron Reduction on Lunar and Asteroidal Surfaces by Micrometeoroids and Solar Wind - Daigo Shoji (The Astrophysical Journal)
Regolith grains and rock surfaces altered by space weathering on the Moon and S-type asteroids contain nanometer-sized metallic iron particles, known as nanophase iron (npFe ^0 ). Several processes have been proposed to explain the reduction of Fe ^2+ and the formation of npFe ^0 , such as vapor deposition due to micrometeoroid impact or solar wind irradiation, and reduction by implanted hydrogen followed by micrometeoroid impact heating. In addition, recent analyses of Chang’e-5 samples suggested disproportionation reduction (3Fe ^2+ → Fe ^0 + 2Fe ^3+ ). However, despite numerous observations and experiments, the exact chemical pathway driving npFe ^0 formation remains controversial. Considering the recent analyses, to investigate the charge evolution of Fe atoms during micrometeoroid impacts and solar wind irradiation, reactive molecular dynamics simulations were conducted. The simulations found that micrometeoroid impacts reduced Fe atoms in fayalite by stripping electrons from O atoms. When the pressure induced by the impact reached approximately 10 GPa, disproportionation reduction, yielding Fe ^3+ in addition to Fe ^0 near the base of the microcrater, was also induced. Proton irradiation also reduced Fe atoms by breaking Fe–O bonds and forming O–H bonds. This result shows that neutral iron atoms can be produced even in environments without significant vaporization as the Chang’e-5 samples indicate. However, in the simulations, the reduced Fe atoms did not aggregate into npFe ^0 particles. The simulations in this work consider the potential derived from the crystal structure of olivine. To simulate the formation of npFe ^0 particles, a different potential may be needed, which requires further studies.